Mineralogical controls of the oceanic nickel cycle - Lena Chen; Autum R. Downey; Corey Archer; Susan H. Little; William B. Homoky; Caroline L. Peacock (Nature Communications)
Abstract Transition metals and their isotopes are promising paleo-productivity proxies, but their utility depends on understanding their cycling between sediment and seawater. Using nickel (Ni) as an example, we show how manganese (Mn) minerals control its isotopic composition in oxic marine sediments. By analysing synthetic and natural samples, and simulating sediment diagenesis, we find that most Ni isotope variability in modern Mn-rich sediments is driven by the relative contribution of two bonding mechanisms – adsorption to and structural incorporation into Mn oxides – which evolve during Mn mineral aging and transformation. We also find that isotopically heavy Ni is preferentially released during transformation. This supports a conceptual model where Mn mineral aging and transformation co-modify sediment and seawater Ni isotopes. Using isotope mass-balance we explore the sensitivity of seawater Ni isotope archives to redox change. We suggest that Mn mineral processes are important for any metal isotope proxy whose cycling is coupled to Mn mineral formation.